“The contemporary Significance of philosophical education” - Iminov Odilbek Nabidjanovich (Scientific Trends, 2025)
This article explores the contemporary significance of philosophical education in the development of both society and the individual. It highlights philosophy’s essential role in fostering critical thinking, moral values, and social responsibility. In the context of globalization, socio-political transformation, and rapid technological progress, philosophical education emerges as a vital means of cultivating critical reasoning, moral and spiritual growth, and addressing social and economic challenges. The paper underscores the importance of philosophical education in shaping ethical and legal approaches to various social issues. It also examines how globalization and digital technologies—particularly online learning platforms—expand the accessibility and impact of philosophical education among youth and adults alike. Furthermore, the study provides a scientific analysis of the future prospects of philosophical education, emphasizing its integration with innovative pedagogical strategies and modern technologies. Overall, this research contributes to a deeper understanding of the enduring value of philosophical education and its evolving role in shaping modern society.
Keywords: philosophical education, critical thinking, moral values, social responsibility, globalization, modern pedagogy, technological development, online education, interdisciplinary approach, spiritual development, societal progress, innovative educational models, virtual platforms, personal development, philosophical knowledge, moral education, the role of philosophy, intellectual growth.